Family, Academic, and Peer Group Predictors of Adolescent Pregnancy Expectations and Young Adult Childbearing. (March 2018) - Smith, Chelsea
Compared with previous generations, today's young people increasingly delay parenthood. Having children in the late teens and early 20s is thus a rarer experience rooted in and potentially leading to the stratification of American families. Understanding why some adolescents expect to do so can illuminate how stratification unfolds. Informed by theories of the life course, social control, and reasoned action, this study used the National Longitudinal Survey of Youth 1997 cohort ( n = 4, 556) to explore outcomes and antecedents of adolescent pregnancy expectations with logistic regressions. Results indicated that those expectations—including neither low nor high (i.e., split) expectations—predicted subsequent childbearing. These apparently consequential expectations were, in turn, most closely associated with youth's academics and peer groups. These findings illustrate how different domains can intersect in the early life course to shape future prospects, and they emphasize split pregnancy expectations reported in a nationally representative sample of young women and men.